Dissecting Anion Effects in Gold(I)‐Catalyzed Intermolecular Cycloadditions. Issue 1 (13th January 2014) - Homs, Anna; Obradors, Carla; Lebœuf, David; Echavarren, Antonio M.
Abstract From a series of gold complexes of the type [t‐BuXPhosAu(MeCN)]X (X=anion), the best results in intermolecular gold(I)‐catalyzed reactions are obtained with the complex with the bulky and soft anion BAr4F− [BAr4F−=3, 5‐bis(trifluoromethyl)phenylborate] improving the original protocols by 10–30% yield. A kinetic study on the [2+2] cycloaddition reaction of alkynes with alkenes is consistent with an scenario in which the rate‐determining step is the ligand exchange to generate the (η2‐phenylacetylene)gold(I) complex. We have studied in detail the subtle differences that can be attributed to the anion in this formation, which result in a substantial decrease in the formation of unproductive σ, π‐(alkyne)digold(I) complexes by destabilizing the conjugated acid formed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>